Rekonstruksi Lingkungan Prasejarah Situs Gua Pawon, Jawa Barat Berdasarkan Kajian Identifikasi Gigi Hewan - Namira, Adinda Tasya; Permana, R. Cecep Eka; Yondri, Lutfi (Badan Riset dan Inovasi Nasional, 2022)
Excavations at the Pawon Cave Site in 2019 and 2021 from boxes T2U1, T2S1, T3U1, T3S1, and T4S1 led to the discovery of 976 specimens of animal teeth that could be used to reconstruct the past of the Pawon’s Cave Site environment. To determine the level of animal taxa to the location of the teeth, taxonomic and anatomical analyses were carried out, while environmental reconstruction was carried out through environmental analysis based on the distribution of faunal functional groups by Julien Louys (2012). The research method consists of six steps, namely formulation, implementation, data collection, data processing, analysis, and interpretation. As a result, 120 individual animals from 13 different families were found at the Pawon Cave site with the dominance of the Cercopithecidae family in each four units of analysis. However, it is also necessary to the contribution of protein produced, so that large animals (megafauna), such as the Families Suidae, Bovidae, and Cervidae, have more potential to become main game animals for consumption, while the Families Cercopithecidae and Hystricidae become a complement to a variety of foods consumed. In addition, jewelry from shark teeth and canine teeth of Carnivora, Cercopithecidae and Suidae were also found with traces of modification in the form of perforation of the roots of the teeth and sharpening of the dental crowns. Thus, the human inhabitants of Pawon Cave are hunters who can utilize all the potential of animals from terrestrial, arboreal and aquatic habitats around the Pawon’s Cave Site.